Shelley Holmes Animal Trainer - Morgan, Michaela (Oxford Oxford University Press, 2014)
Shelley has a great idea in Shelley Holmes Animal Trainer. She decides to be an animal trainer. Shelley is sure it will be easy, but when she tries to train her dog, Dustbin, things don't quite go to plan. TreeTops Fiction contains engaging novels from top authors and illustrators with the variety children need to develop a love of reading!
Include Illustrations